2013
DOI: 10.5398/medpet.2013.36.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Cortisol, Triiodothyronine, Thyroxine and Neutrophil/Lymphocyte Ratio as Stress Indicators in Swamp Buffaloes 15 Days Post-Transportation

Abstract: Transportation may cause stress that affects livestock’s health. This research was conducted to observe the effect of transportation on the profiles of blood cortisol, triiodothyronine (T3), thyroxine (T4) and neutrophil/lymphocyte (N/L) ratio as stress indicators during 15 days post-transportation. Four females swamp buffaloes, 2-yr-old were used in this research. The animals were transported using an open truck, along 15 kilometers distance for 2 h. During acclimatization, the animals were fed grass twice a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Maheshwari et al. () has also reported a gradually increase in cortisol concentration from day 3 after transportation and the second peak of this hormone on day 4. Higher cortisol level in the PTG2 group of the present study might correspond with the second peak after transportation which reported in buffaloes (Maheshwari et al., ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Maheshwari et al. () has also reported a gradually increase in cortisol concentration from day 3 after transportation and the second peak of this hormone on day 4. Higher cortisol level in the PTG2 group of the present study might correspond with the second peak after transportation which reported in buffaloes (Maheshwari et al., ).…”
Section: Discussionmentioning
confidence: 89%
“…Maheshwari et al. () also showed a significant relationship between transportation and an increase in cortisol level in buffaloes. They demonstrated that cortisol showed the highest elevation on day‐1 after transportation when animals just arrived to the location and fell down to the normal level on day‐2.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Transportasi ternak merupakan salah satu penyebab stres pada ternak (Saeb et al, 2010;Astuti et al, 2010) yang dapat mepengaruhi kesehatan ternak (Maheshwari et al, 2013), kesejahteraan hewan dan besaran ongkos ekonomi (Saeb et al, 2010), kualitas karkas (Minka dan Ayo, 2010), morbiditas dan mortalitas ternak (Fazio dan Ferlazzo, 2003). Perubahan kondisi lingkungan pemicu stres selama transportasi tersebut memicu perubahan fisiologis sebagai bentuk adaptasi ternak.…”
Section: Pendahuluanunclassified